Practical experience in organizing transport links between the city and the airport and its impact on the formation of transport interchanges - Pustovoit, Ruslan (Theory and practice of design, 2022)
The purpose of the study is to analyze foreign and domestic experience in the organization of transport links between the city and the airport and identify its impact on the formation of transport interchanges. The article presents the generalized results of the current state of the transport system of the airport and the city and reveals the factors influencing the transport connection on the formation of transport interchanges. The directions of improvement and development of the transport system of airports are considered. Based on the analysis, the method of choosing transport between the city and the airport based on passenger traffic is derived. The article is aware of its purpose, namely, presents the generalized results of the state of the transport system of the airport and the city, identifies factors influencing the formation of transport interchanges at airports. Analysis of the current development of railway transit of multi-airport systems of world agglomerations shows that airport transport systems are integrated into the railway systems of urban agglomerations and form efficient transport interchanges as a combination of different types of railway transport. Foreign experience of railway transport has shown that today Ukrainian airports have just begun their movement to the level of world-class organization of railway connections and their integration into urban and suburban transport. The study revealed the main factors influencing the formation of interchanges at airports. These include: the presence of transit lines of railway transport within the airport; inclusion of the airport transport system in suburban and urban transport; variety of automobile and railway types of vehicles (buses, taxis, subways, electric vehicles, monorails).